2018
DOI: 10.15171/ajmb.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance, Endurance, and Concurrent Exercise on Oxidative Stress Markers and the Histological Changes of Intestine After Morphine Withdrawal in Rats

Abstract: Objectives: The aim of this study was to evaluate the effects of resistance, endurance, and concurrent exercise on oxidative stress markers and histological changes of the intestine after morphine withdrawal in rats. Methods: A total of 30 male Wistar rats were randomly divided into 5 groups (n=6) including healthy control, withdrawal (rat received morphine for 21 days and 8 weeks of withdrawal period), withdrawal + endurance exercises, withdrawal + resistance exercises, and withdrawal + concurrent exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In addition, treating with ascorbic acid as an antioxidant substance leads to reduce oxidative stress conditions in the liver of rats. Also, it was reported that morphine decreases anti-oxidant and glutathione enzymes in the intestine and liver of rats, which is consistent with our study results (Nagamatsu et al, 1983;Salehi et al, 2018;Sumathi and Niranjali Devaraj, 2009).…”
Section: Assessing Dna Damage Level (8-ohdg)supporting
confidence: 93%
See 1 more Smart Citation
“…In addition, treating with ascorbic acid as an antioxidant substance leads to reduce oxidative stress conditions in the liver of rats. Also, it was reported that morphine decreases anti-oxidant and glutathione enzymes in the intestine and liver of rats, which is consistent with our study results (Nagamatsu et al, 1983;Salehi et al, 2018;Sumathi and Niranjali Devaraj, 2009).…”
Section: Assessing Dna Damage Level (8-ohdg)supporting
confidence: 93%
“…Similarly, Mallikarjuna et al (2009) indicated that regular exercise training significantly reversed the increase MDA and decreases GSH and ascorbic acid induced by ethanol drinking. Also it was reported that endurance, resistance and concurrent exercise significantly normalized oxidative stress and the morphological changes of the intestine in withdrawal rats (Salehi et al, 2018). It is reported that continuous and interval training decreased oxidative damage in erythrocytes of the studied humans (Yunus et al, 2018).…”
Section: Discussionmentioning
confidence: 90%